Hrvati u Njemačkoj pred izazovima integracije - Borić, Gojko (Array, 2008)
The future of a united Europe will be founded on the preservation of individual national cultures with a certain amount of the internationalism of European unity. Croatians in Germany can practice this brilliantly, especially their second and third generations if they manage to hold on to their own language, culture and national individuality while gaining the language, culture and European specificity of the country in which they live. Foreigners in Germany, among which there are 400,000 Croatians from the Republic of Croatia and Bosnia & Herzegovina, find themselves between the hammer of Germany Leitkulture and the anvil of multiculturalism. This is hard to survive, but it is possible to resist and to shape one's own identity complex within a coexistence. Germans request of foreigners, not only in their appeals but through legislation that encourages it, that they integrate completely into German society, which is quite understandable, as they wish to prevent the creation of so-called parallel societies, a kind of guest worker ghettoization. Of Croatians it can be said that they have almost completely integrated into German society, but it is often difficult to find a line of distinction between integration and assimilation. And it should be visible to all, foreigners and Germans. Integration means that foreigners should be subject to German laws and rules of social behaviour. The leaders of Croatian associations and societies have yet to find a method whereby their youth would be more effectively involved in Croatian social structures in Germany, and they require significantly greater assistance from the homeland to do so.